Pengaruh Edukasi Kegawatdaruratan Hipertensi Terhadap Pengetahuan Keluarga dengan Hipertensi - Rosmina Muhidin; Suwandi I. Luneto; Rahmat Hidayat Djalil (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a blood vessel disease that has a high risk of causing serious complications and death. The role of the family in preventing complications and death due to hypertension is very important, especially in emergency conditions. One effort to reduce this risk is through health education. This study aims to determine the effect of hypertension emergency education on the knowledge of families of hypertension with at the Pratama Agung Amanah Ternate General Clinic. This study used a pre-experimental method with a one group pre-test post-test design. The sample used was 30 respondents selected through total sampling. Data were collected using a questionnaire and then analyzed. The Mc. Nemar statistical test showed significant results with a p value ≤ 0.001 which indicated a significant effect between hypertension emergency education on the knowledge of families of hypertension sufferers. The conclusion of this study shows that hypertension emergency education has a positive effect on increasing the knowledge of families of hypertension with. The results of this study are expected to increase understanding of the importance of handling hypertension emergencies as an initial step in prevention.